Hand–arm bimanual intensive therapy and daily functioning of children with bilateral cerebral palsy: a randomized controlled trial. (19th July 2020) - Figueiredo, Priscilla R P; Mancini, Marisa C; Feitosa, Aline M; Teixeira, Claudia M M F; Guerzoni, Vanessa P D; Elvrum, Ann‐Kristin G; Ferre, Claudio L; Gordon, Andrew M; BrandÃo, Marina B
Abstract : Aim: To examine the efficacy of Hand–Arm Bimanual Intensive Therapy (HABIT) on daily functioning, unimanual dexterity, and bimanual performance of children with bilateral cerebral palsy (CP) compared with customary care. Method: Forty‐one children with bilateral CP, aged 4 to 16 years, classified in levels I to III of the Manual Ability Classification System, were randomly assigned to HABIT (90h) ( n =21) or to customary care (4.5h) ( n =20). Participants' daily functioning (Pediatric Evaluation of Disability Inventory [PEDI], Canadian Occupational Performance Measure [COPM]), unimanual dexterity (Jebsen–Taylor Test of Hand Function, Box and Blocks Test [BBT]), and bimanual performance (Both Hands Assessment) were assessed pre‐, post‐, and 6 months after the intervention. Linear mixed‐effects models were used for inferential analysis. Results: Children participating in HABIT showed greater improvements in daily functioning (COPMperformance : χ 1 2 =9.50, p <0.01; COPMsatisfaction : χ 1 2 =5.07, p <0.05; PEDIfunctional skills : χ 1 2 =6.81, p <0.01; PEDIcaregiver assistance : χ 1 2 =6.23, p <0.05) and in the dexterity of the dominant hand (BBT: χ 1 2 =3.99, p <0.05) compared with children maintaining customary care. Group or time effects did not explain any variance in bimanual performance or in the dexterity of the non‐dominant hand. Interpretation: HABIT may be beneficial for children with bilateral CP, with benefits evidenced for daily functioning outcomes. What this paper adds: Hand–Arm Bimanual Intensive Therapy (HABIT) improved daily functioning of children with bilateral cerebral palsy (CP). Bimanual performance, measured by the Both Hands Assessment, did not change after HABIT in children with bilateral CP. Children with asymmetric and symmetric hand use exhibited similar improvements after HABIT. What this paper adds: Hand–Arm Bimanual Intensive Therapy (HABIT) improved daily functioning of children with bilateral cerebral palsy (CP). Bimanual performance, measured by the Both Hands Assessment, did not change after HABIT in children with bilateral CP. Children with asymmetric and symmetric hand use exhibited similar improvements after HABIT. This article is commented on by Hoare on page 1231 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Video Podcast: https://youtu.be/Gq2gdjUm4jw Terapia bimanual intensiva mano‐brazo y funcionamiento diario de niños con parálisis cerebral bilateral: un ensayo controlado aleatorio: Objetivo: Examinar la eficacia de la terapia bimanual intensiva mano‐brazo (HABIT) en el funcionamiento diario, la destreza unimanual y el rendimiento bimanual de los niños con parálisis cerebral bilateral (PC) en comparación con la atención habitual. Método: Cuarenta y un niños con PC bilateral, de 4 a 16 años, clasificados en los niveles I a III del Sistema de Clasificación de Habilidad Manual, fueron asignados aleatoriamente a HABIT (90h) (n = 21) o a la atención habitual (4.5h) (n = 20). Las siguientes escalas de evaluación se evaluaron antes, después y 6 meses después de la intervención: Funcionamiento diario de los participantes (Inventario de evaluación pediátrica de discapacidad [PEDI], Medida de desempeño ocupacional canadiense [COPM]), destreza unimanual (Prueba de Jebsen‐Taylor de la función de la mano, Prueba de caja y bloques [BBT]) y rendimiento bimanual (Evaluación de ambas manos). Se utilizaron modelos lineales de efectos mixtos para el análisis inferencial. Resultados: Los niños que participaron en HABIT mostraron mejoras mayores en el funcionamiento diario (rendimiento de COPM: χ21 = 9.50, p <0.01; satisfacción de COPM: χ21 = 5.07, p <0.05; PED Habilidades funcionales: χ21 = 6.81, p <0.01; Asistencia del cuidador PED: χ21 = 6.23, p <0.05) y en la destreza de la mano dominante (BBT: χ21 = 3.99, p <0.05) en comparación con los niños que mantienen la atención habitual. Los efectos grupales o temporales no explicaron ninguna variación en el rendimiento bimanual o en la destreza de la mano no dominante. Interpretación: HABIT puede ser beneficioso para los niños con PC bilateral, con beneficios evidenciados para los resultados del funcionamiento diario. Terapia intensiva bimanual mão‐braço e funcionamento diário de crianças com paralisia cerebral bilateral: um ensaio clínico randomizado: Objetivo: Examinar a eficácia do Treino Intensivo Bimanual de Braço e Mão (HABIT) na funcionalidade diária, destreza unimanual e desempenho bimanual de crianças com paralisia cerebral bilateral (PC) em comparação com cuidado convencional. Método: Quarenta e uma crianças com PC bilateral, com idade entre 4 e 16 anos, classificadas nos níveis I a III do Sistema de Classificação da Habilidade Manual, foram alocadas aleatoriamente no grupo HABIT (90h) (n = 21) ou no grupo de cuidado convencional (4, 5h) (n = 20). A funcionalidade diária dos participantes (Inventário de Avaliação Pediátrica de Incapacidade [PEDI], Medida Canadense de Desempenho Ocupacional [COPM]), a destreza unimanual (Teste de Função Manual Jebsen – Taylor, Box and Block Test [BBT]) e desempenho bimanual (Both Hands Assessment) foram avaliados antes, imediatamente após e 6 meses após a intervenção. Modelos lineares mistos foram utilizados para análise inferencial. Resultados: As crianças participantes do HABIT apresentaram melhora superior na funcionalidade diária (COPMdesempenho: χ21=9, 50, p<0, 01; COPMsatisfação: χ21= 5, 07, p<0, 05; PEDIhabilidades funcionais: χ21=6, 81, p<0, 01; PEDIassistência do cuidador: χ21=6, 23, p<0, 05) e na destreza da mão dominante (BBT: χ21=3, 99, p<0, 05) em comparação às crianças que mantiveram cuidado convencional. Os efeitos de grupo ou de tempo não explicaram qualquer variância no desempenho bimanual ou na destreza da mão não dominante. Interpretação: Crianças com PC bilateral podem se beneficiar do HABIT no que se refere a desfechos de funcionalidade diária.